An algorithm to discover any change with the messages or documents which is sent with the internet. - H. Kassim, Najat (University of Thi-Qar Journal of Science, 2019)
This research introduce new algorithm to discover any change in the sender message. This algorithm is programmed with visual Basic language. This algorithm is building from inputing message by the sender to find key or (password) for encoding the sender information , which is append to the original message and will be represents the message digital signature. the algorithm of key will be search to find symbols that represents middle of any word ,this symbols will be concatenation to produced key in Ascii codes , which sum to produced key number that is added to each Ascii code from the sender information, as result ,every symbol is converted to Ascii code to produced new code append with message. the receiver will be produced key with the same algorithm above, then using it to decode message signature , by using the reverse algorithm of encoding , if this document or message is right, so the user information is read to know him .otherwise, the receiver will not decode this information so ,may be this document or message changed.